Maturation of Corpus Callosum Anterior Midbody Is Associated with Neonatal Motor Function in Eight Preterm-Born Infants. (28th January 2013) - Mathew, Preethi; Pannek, Kerstin; Snow, Pamela; D'Acunto, M. Giulia; Guzzetta, Andrea; Rose, Stephen E.; Colditz, Paul B.; Finnigan, Simon
Abstract : Background . The etiology of motor impairments in preterm infants is multifactorial and incompletely understood. Whether corpus callosum development is related to impaired motor function is unclear. Potential associations between motor-related measures and diffusion tensor imaging (DTI) of the corpus callosum in preterm infants were explored. Methods . Eight very preterm infants (gestational age of 28–32 weeks) underwent the Hammersmith neonatal neurological examination and DTI assessments at gestational age of 42 weeks. The total Hammersmith score and a motor-specific score (sum of Hammersmith motor subcategories) were calculated. Six corpus callosum regions of interest were defined on the mid-sagittal DTI slice—genu, rostral body, anterior midbody, posterior midbody, isthmus, and splenium. The fractional anisotropy (FA) and mean diffusivity (MD) of these regions were computed, and correlations between these and Hammersmith measures were sought. Results . Anterior midbody FA measures correlated positively with total Hammersmith (rho = 0.929, P = 0.001 ) and motor-specific scores (rho = 0.857, P = 0.007 ). Total Hammersmith scores also negatively correlated with anterior midbody MD measures (rho = − 0.714, P = 0.047 ). Discussion . These results suggest the integrity of corpus callosum axons, particularly anterior midbody axons, is important in mediating neurological functions. Greater callosal maturation was associated with greater motor function. Corpus callosum DTI may prove to be a valuable screening or prognostic marker.